Multilayer ceramic electronic components
The multilayer ceramic electronic component addresses the trade-off between mechanical strength and ESR by using a conductive resin layer with a balanced metal and resin composition to improve conductivity and absorb stress, preventing cracks.
Patent Information
- Application Number
- JP2023563607
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-26
- Filing Date
- 2022-11-09
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-11-09
AI Technical Summary
Multilayer ceramic electronic components face a trade-off between improving mechanical strength and ESR characteristics due to the use of epoxy thermosetting resin layers, which increase hardness and elastic modulus while reducing electrical conductivity.
A multilayer ceramic electronic component design with a conductive resin layer containing a specific ratio of metal and resin components, where the end face side conductive resin layer has a higher metal content for improved conductivity and the adjacent layer has a higher resin content for elasticity, allowing stress to be released and cracks to be suppressed.
The design achieves desired ESR characteristics while enhancing mechanical strength by allowing stress to be absorbed and cracks to be prevented, even under harsh environmental conditions.
Smart Images

Figure 0007616420000003 
Figure 0007616420000004 
Figure 0007616420000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a multilayer ceramic electronic component. [Background technology]
[0002] In recent years, multilayer ceramic electronic components, such as multilayer ceramic capacitors, have come to be used in harsher environments than ever before. For example, electronic components used in mobile devices such as mobile phones and portable music players are required to withstand impacts when dropped. Specifically, it is necessary to ensure that the multilayer ceramic electronic components do not fall off the mounting board or that cracks do not occur in the multilayer ceramic electronic components even when subjected to an impact from being dropped.
[0003] Furthermore, electronic components used in in-vehicle devices such as ECUs (Electronic Control Units) are required to withstand the impact of thermal cycles.Specifically, it is necessary to prevent cracks from occurring in multilayer ceramic electronic components even when they are subjected to bending stress caused by the thermal expansion and contraction of the mounting board during thermal cycles.
[0004] In response to this, it has been proposed to use a thermosetting conductive resin paste for the external electrodes of multilayer ceramic electronic components. For example, in Patent Document 1, an epoxy-based thermosetting resin layer is formed between the conventional electrode layer and Ni plating, as a measure to prevent cracks from occurring in the capacitor body even in harsh environments (improved resistance to bending).
[0005] In such a configuration, when stress occurs due to an impact when dropped, or flexural stress occurs due to the thermal expansion and contraction of the mounting board due to a thermal cycle, the stress (distortion of the mounting board) is transmitted to the mounting board by causing separation between the electrode layer and the epoxy thermosetting resin layer starting from the tip of the epoxy thermosetting resin layer, thereby dissipating the stress and preventing cracks from occurring in the capacitor body. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 11-162771 Summary of the Invention [Problem to be solved by the invention]
[0007] However, the metal components contained in the epoxy thermosetting resin layer increase the hardness and elastic modulus of the resin electrode, which is detrimental to improving mechanical strength, and the resin components contained in the epoxy thermosetting resin layer are not conductive, which is detrimental to ESR (equivalent series resistance) characteristics. Therefore, in a multilayer ceramic electronic component having an epoxy thermosetting resin layer, there is a trade-off between the improvement in mechanical strength and the ESR characteristics, so it may be difficult to effectively achieve both of these characteristics.
[0008] Therefore, a primary object of the present invention is to provide a multilayer ceramic electronic component that has desired ESR characteristics while maintaining the mechanical strength of the multilayer ceramic electronic component. [Means for solving the problem]
[0009] A multilayer ceramic electronic component according to the present invention includes a laminate including a plurality of laminated ceramic layers, the laminate having first and second main surfaces opposing each other in a height direction, first and second side surfaces opposing each other in a width direction perpendicular to the height direction, and first and second end surfaces opposing each other in a length direction perpendicular to the height and width directions; a first internal electrode layer disposed on the plurality of ceramic layers and exposed at the first end surface; a second internal electrode layer disposed on the plurality of ceramic layers and exposed at the second end surface; a first external electrode electrically connected to the first internal electrode layer and disposed on the first end surface, a portion of the first main surface, a portion of the second main surface, a portion of the first side surface, and a portion of the second side surface; and a second external electrode electrically connected to the second internal electrode layer and disposed on the second end surface, a portion of the first main surface, a portion of the second main surface, a portion of the first side surface, and a portion of the second side surface. a conductive resin layer including a first external electrode and a second external electrode, the first external electrode and the second external electrode including a base electrode layer containing a metal component and a glass component, a conductive resin layer including a metal component and a resin component that is disposed on the base electrode layer, and a plating layer that is disposed on the conductive resin layer, the conductive resin layer including an end surface-side conductive resin layer portion located on the first end surface and the second end surface, and an adjacent conductive resin layer portion extending from an end of the end surface-side conductive resin layer portion and positioned on the first main surface, the second main surface, the first side surface, and the second side surface, the content ratio of the resin component contained in the adjacent conductive resin layer portion is higher than the content ratio of the resin component contained in the end surface-side conductive resin layer portion, and the content ratio of the resin component in the end surface-side conductive resin layer portion is 10% or more and 60% or less.
[0010] In the multilayer ceramic electronic component according to the present invention, the first external electrode and the second external electrode have a base electrode layer containing a metal component and a glass component, a conductive resin layer containing a metal component and a resin component arranged on the base electrode layer, and a plating layer arranged on the conductive resin layer, and the conductive resin layer has an end face-side conductive resin layer portion located on the first end face and the second end face, and an adjacent conductive resin layer portion extending from an end of the end face-side conductive resin layer portion and located on the first main face, the second main face, the first side face, and the second side face, and when the sum of the resin component and the metal component in the end face-side conductive resin layer portion and the adjacent conductive resin layer portion is taken as 100%, the content ratio of the resin component contained in the adjacent conductive resin layer portion is higher than the content ratio of the resin component contained in the end face-side conductive resin layer portion, and the content ratio of the resin component in the end face-side conductive resin layer portion is 10% or more and 60% or less. Therefore, the end-side conductive resin layer part having a high content of metal components can improve the conductivity, and as a result, the ESR of the multilayer ceramic electronic component can be reduced. In addition, the adjacent conductive resin layer part having a high content of resin components can have sufficient elasticity, so that when a deflection stress occurs due to stress caused by the impact of a drop or thermal expansion and contraction of the mounting board caused by a thermal cycle, the stress transmitted to the mounting board (distortion of the mounting board) can be peeled off between the base electrode layer and the adjacent conductive resin layer, or between the plating layer and the adjacent conductive resin layer part, starting from the tip of the adjacent conductive resin layer part, or the interior of the adjacent conductive resin layer part can be cohesively broken. This makes it possible to release the stress and suppress the occurrence of cracks in the laminate, thereby improving the mechanical strength of the multilayer ceramic electronic component. Effect of the Invention
[0011] According to the present invention, it is possible to provide a multilayer ceramic electronic component that has the desired ESR characteristics while maintaining the mechanical strength of the multilayer ceramic electronic component.
[0012] The above and other objects, features and advantages of the present invention will become more apparent from the following detailed description of the preferred embodiments of the present invention, which proceeds with reference to the accompanying drawings. [Brief description of the drawings]
[0013] [Figure 1] 1 is an external perspective view showing an example of a multilayer ceramic capacitor as a multilayer ceramic electronic component according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view taken along line II-II in FIG. [Diagram 3] FIG. 2 is a cross-sectional view taken along line III-III in FIG. [Figure 4] FIG. 2 is a schematic cross-sectional view showing the structure of an external electrode. [Diagram 5] 1A is a cross-sectional view taken along line II-II in FIG. 1 showing a structure in which a counter electrode portion of an internal electrode layer of a multilayer ceramic capacitor according to an embodiment of the present invention is divided into two, (b) is a cross-sectional view taken along line II-II in FIG. 1 showing a structure in which a counter electrode portion of an internal electrode layer of a multilayer ceramic capacitor according to the present invention is divided into three, and (c) is a cross-sectional view taken along line II-II in FIG. 1 showing a structure in which a counter electrode portion of an internal electrode layer of a multilayer ceramic capacitor according to the present invention is divided into four. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] 1. Multilayer ceramic capacitors As an example of a multilayer ceramic electronic component according to an embodiment of the present invention, a multilayer ceramic capacitor will be described.
[0015] Fig. 1 is an external perspective view showing an example of a multilayer ceramic capacitor as a multilayer ceramic electronic component according to an embodiment of the present invention. Fig. 2 is a cross-sectional view taken along line II-II in Fig. 1. Fig. 3 is a cross-sectional view taken along line III-III in Fig. 1. Fig. 4 is a schematic cross-sectional view showing the structure of an external electrode.
[0016] As shown in FIGS. 1 to 3, a multilayer ceramic capacitor 10 includes a rectangular parallelepiped laminate 12 and external electrodes 30 disposed on both ends of the laminate 12.
[0017] The laminate 12 has a plurality of laminated ceramic layers 14 and a plurality of internal electrode layers 16 laminated on the ceramic layers 14. Furthermore, the laminate 12 has a first main surface 12a and a second main surface 12b facing the height direction x, a first side surface 12c and a second side surface 12d facing the width direction y perpendicular to the height direction x, and a first end surface 12e and a second end surface 12f facing the length direction z perpendicular to the height direction x and the width direction y. The corners and ridges of the laminate 12 are rounded. The corners are the portions where three adjacent surfaces of the laminate intersect, and the ridges are the portions where two adjacent surfaces of the laminate intersect. In addition, unevenness may be formed on a part or all of the first main surface 12a and the second main surface 12b, the first side surface 12c and the second side surface 12d, and the first end surface 12e and the second end surface 12f. The ceramic layers 14 and the internal electrode layers 16 are stacked in the height direction x.
[0018] As shown in Figures 2 and 3, the laminate 12 has, in the stacking direction connecting the first main surface 12a and the second main surface 12b, an effective layer portion 18 in which multiple internal electrode layers 16 face each other, a first outer layer portion 20a formed from multiple ceramic layers 14 located between the internal electrode layer 16 located closest to the first main surface 12a and the first main surface 12a, and a second outer layer portion 20b formed from multiple ceramic layers 14 located between the internal electrode layer 16 located closest to the second main surface 12b and the second main surface 12b.
[0019] The first outer layer portion 20a is located on the first main surface 12a side of the laminate 12, and is an assembly of a plurality of ceramic layers 14 located between the first main surface 12a and the internal electrode layer 16 closest to the first main surface 12a.
[0020] The second outer layer portion 20b is located on the second main surface 12b side of the laminate 12, and is an assembly of a plurality of ceramic layers 14 located between the second main surface 12b and the internal electrode layer 16 closest to the second main surface 12b.
[0021] The region sandwiched between the first outer layer portion 20a and the second outer layer portion 20b is the effective layer portion 18. The number of ceramic layers 14 to be laminated is not particularly limited, but is preferably 10 to 700, including the first outer layer portion 20a and the second outer layer portion 20b. The thickness of the ceramic layers 14 is preferably 0.5 μm to 15.0 μm.
[0022] The dimensions of the laminate 12 are not particularly limited, but it is preferable that the dimensions do not exceed the dimensions of the multilayer ceramic capacitor 10 , including the thickness of the external electrodes 30 .
[0023] The ceramic layer 14 can be formed of, for example, a dielectric material as the ceramic material. As such a dielectric material, for example, a dielectric ceramic containing a component such as BaTiO3, CaTiO3, SrTiO3, or CaZrO3 can be used. When the above-mentioned dielectric material is contained as a main component, a subcomponent such as a Mn compound, an Fe compound, a Cr compound, a Co compound, or a Ni compound may be added in a smaller amount than the main component depending on the desired characteristics of the laminate 12.
[0024] When a piezoelectric ceramic material is used for the ceramic layers 14, the multilayer ceramic electronic component functions as a piezoelectric component. Specific examples of the piezoelectric ceramic material include PZT (lead zirconate titanate) ceramic materials. When a semiconductor ceramic material is used for the ceramic layers 14, the multilayer ceramic electronic component functions as a thermistor. Specific examples of the semiconductor ceramic material include spinel ceramic materials. When a magnetic ceramic material is used for the ceramic layers 14, the multilayer ceramic electronic component functions as an inductor. When the multilayer ceramic electronic component functions as an inductor, the internal electrode layer 16 becomes a coil-shaped conductor. Specific examples of the magnetic ceramic material include ferrite ceramic materials.
[0025] The thickness of the ceramic layer 14 after firing is preferably 0.5 μm or more and 15 μm or less. The number of the laminated ceramic layers 14 is preferably 10 to 700. The number of the ceramic layers 14 is the total number of the ceramic layers 14 in the effective layer portion 18 and the ceramic layers 14 in the first outer layer portion 20a and the second outer layer portion 20b.
[0026] The laminate 12 has, for example, a plurality of substantially rectangular first internal electrode layers 16a and a plurality of second internal electrode layers 16b as the plurality of internal electrode layers 16. The plurality of first internal electrode layers 16a and the plurality of second internal electrode layers 16b are embedded so as to be alternately arranged at equal intervals with the ceramic layers 14 sandwiched therebetween along the height direction x of the laminate 12.
[0027] The first internal electrode layer 16a is disposed on the multiple ceramic layers 14 and is located inside the laminate 12. The first internal electrode layer 16a has a first opposing electrode portion 22a facing the second internal electrode layer 16b, and a first extraction electrode portion 24a located on one end side of the first internal electrode layer 16a and extending from the first opposing electrode portion 22a to the first end face 12e of the laminate 12. An end portion of the first extraction electrode portion 24a is extended to the surface of the first end face 12e and exposed from the laminate 12.
[0028] The shape of the first opposing electrode portion 22a of the first internal electrode layer 16a is not particularly limited, but is preferably rectangular in plan view. However, the corners in plan view may be rounded or may be formed at an angle in plan view (tapered). Also, the corners may be tapered in plan view with an inclination toward either side.
[0029] The shape of the first extraction electrode portion 24a of the first internal electrode layer 16a is not particularly limited, but is preferably rectangular in plan view. However, the corners in plan view may be rounded or may be formed at an angle in plan view (tapered). Also, the corners may be tapered in plan view with an inclination in either direction.
[0030] The width of the first opposing electrode portion 22a of the first internal electrode layer 16a and the width of the first extraction electrode portion 24a of the first internal electrode layer 16a may be formed to be the same width, or one of the widths may be formed to be narrower.
[0031] The second internal electrode layer 16b is disposed on the multiple ceramic layers 14 and is located inside the laminate 12. The second internal electrode layer 16b has a second opposing electrode portion 22b that faces the first internal electrode layer 16a, and a second extraction electrode portion 24b that is located on one end side of the second internal electrode layer 16b and extends from the second opposing electrode portion 22b to the second end face 12f of the laminate 12. An end of the second extraction electrode portion 24b is extended to the surface of the second end face 12f and is exposed from the laminate 12.
[0032] The shape of the second opposing electrode portion 22b of the second internal electrode layer 16b is not particularly limited, but is preferably rectangular in plan view. However, the corners in plan view may be rounded or may be formed obliquely in plan view (tapered). Also, the shape may be tapered in plan view with an inclination toward either side.
[0033] The shape of the second extraction electrode portion 24b of the second internal electrode layer 16b is not particularly limited, but is preferably rectangular in plan view. However, the corners in plan view may be rounded or may be formed at an angle in plan view (tapered). Also, the shape may be tapered in plan view with an inclination toward either side.
[0034] The width of the second opposing electrode portion 22b of the second internal electrode layer 16b and the width of the second extraction electrode portion 24b of the second internal electrode layer 16b may be formed to be the same width, or one of the widths may be formed to be narrower.
[0035] Furthermore, as shown in FIG. 2, the laminate 12 includes ends 28 (hereinafter referred to as "L gaps") 28 of the laminate 12 formed between the end of the first internal electrode layer 16a opposite the first extraction electrode portion 24a and the second end face 12f, and between the end of the second internal electrode layer 16b opposite the second extraction electrode portion 24b and the first end face 12e.
[0036] As shown in FIG. 3, the laminate 12 includes a side portion (hereinafter referred to as a "W gap") 26 of the laminate 12 formed between one end in the width direction y of the first opposing electrode portion 22a and the second opposing electrode portion 22b and the first side surface 12c, and between the other end in the width direction y of the first opposing electrode portion 22a and the second opposing electrode portion 22b and the second side surface 12d.
[0037] The first internal electrode layer 16a and the second internal electrode layer 16b can be made of an appropriate conductive material, such as a metal such as Ni, Cu, Ag, Pd, or Au, or an alloy containing at least one of these metals, such as an Ag-Pd alloy.
[0038] The thickness of each of the internal electrode layers 16, i.e., the first internal electrode layers 16a and the second internal electrode layers 16b, is preferably 0.2 μm or more and 2.0 μm or less. The total number of the first internal electrode layers 16a and the second internal electrode layers 16b is preferably 10 or more and 700 or less.
[0039] As shown in FIGS. 1 to 3, external electrodes 30 are disposed on the first end face 12e side and the second end face 12f side of the laminate 12.
[0040] The external electrode 30 includes a first external electrode 30a and a second external electrode 30b.
[0041] The first external electrode 30a is connected to the first internal electrode layer 16a and is disposed on at least the surface of the first end face 12e. The first external electrode 30a also extends from the first end face 12e of the laminate 12 and is disposed on a part of the first main face 12a, a part of the second main face 12b, a part of the first side face 12c, and a part of the second side face 12d. In this case, the first external electrode 30a is electrically connected to the first extraction electrode portion 24a of the first internal electrode layer 16a.
[0042] The second external electrode 30b is connected to the second internal electrode layer 16b and is disposed on at least the surface of the second end face 12f. The second external electrode 30b also extends from the second end face 12f and is disposed on a part of the first main face 12a, a part of the second main face 12b, a part of the first side face 12c, and a part of the second side face 12d. In this case, the second external electrode 30b is electrically connected to the second extraction electrode portion 24b of the second internal electrode layer 16b.
[0043] In the laminate 12, a capacitance is formed by the first opposing electrode portion 22a of the first internal electrode layer 16a and the second opposing electrode portion 22b of the second internal electrode layer 16b facing each other via the ceramic layer 14. Therefore, a capacitance can be obtained between the first external electrode 30a to which the first internal electrode layer 16a is connected and the second external electrode 30b to which the second internal electrode layer 16b is connected, and the characteristics of a capacitor are exhibited.
[0044] 5, the laminate 12 shown in FIG. 1 may have a structure in which, in addition to the first internal electrode layer 16a and the second internal electrode layer 16b, a floating internal electrode layer 16c that is not drawn out to either the first end face 12e or the second end face 12f is provided, and the floating internal electrode layer 16c divides the opposing electrode portion 22c into a plurality of portions. For example, the structure may be a two-part structure shown in FIG. 5(a), a three-part structure shown in FIG. 5(b), or a four-part structure shown in FIG. 5(c), or it goes without saying that a structure of four or more parts may be used. In this way, by dividing the opposing electrode portion 22c into a plurality of portions, a plurality of capacitor components are formed between the opposing internal electrode layers 16a, 16b, and 16c, and these capacitor components are connected in series. Therefore, the voltage applied to each capacitor component is lowered, and the multilayer ceramic capacitor 10 can have a high withstand voltage.
[0045] The external electrode 30 includes a base electrode layer 32 including a metal component and a glass component, a conductive resin layer 34 including a metal component and a resin component disposed on the base electrode layer 32, and a plating layer 36 disposed on the conductive resin layer 34. The first external electrode 30a includes a first base electrode layer 32a including a metal component and a glass component, a first conductive resin layer 34a including a metal component and a resin component disposed on the first base electrode layer 32a, and a first plating layer 36a disposed on the first conductive resin layer 34a. The second external electrode 30b includes a second base electrode layer 32b including a metal component and a glass component, a second conductive resin layer 34b including a metal component and a resin component disposed on the second base electrode layer 32b, and a second plating layer 36b disposed on the second conductive resin layer 34b.
[0046] The base electrode layer 32 includes a first base electrode layer 32a and a second base electrode layer 32b.
[0047] The first base electrode layer 32a is connected to the first internal electrode layer 16a and disposed on the surface of the first end face 12e. The first base electrode layer 32a also extends from the first end face 12e and is disposed on a part of the first main face 12a, a part of the second main face 12b, a part of the first side face 12c, and a part of the second side face 12d. In this case, the first base electrode layer 32a is electrically connected to the first lead electrode portion 24a of the first internal electrode layer 16a.
[0048] The second base electrode layer 32b is connected to the second internal electrode layer 16b and disposed on the surface of the second end face 12f. The second base electrode layer 32b also extends from the second end face 12f and is disposed on a part of the first main face 12a, a part of the second main face 12b, a part of the first side face 12c, and a part of the second side face 12d. In this case, the second base electrode layer 32b is electrically connected to the second extraction electrode portion 24b of the second internal electrode layer 16b.
[0049] The base electrode layer 32 includes at least one selected from a baked layer, a thin film layer, etc. Hereinafter, each configuration when the base electrode layer 32 is the above-mentioned baked layer or thin film layer will be described.
[0050] The baking layer includes a glass component and a metal component. The glass component of the baking layer includes at least one selected from B, Si, Ba, Mg, Al, Li, etc. The metal component of the baking layer includes at least one selected from Cu, Ni, Ag, Pd, Ag-Pd alloy, Au, etc., for example. The baking layer is formed by applying a conductive paste containing a glass component and a metal component to the laminate 12 and baking it. The baking layer may be a layered chip having an internal electrode layer 16 and a ceramic layer 14 and a conductive paste applied to the laminated chip, which are simultaneously baked, or a layered chip having an internal electrode layer 16 and a ceramic layer 14 is baked to obtain a laminate, and then a conductive paste is baked on the laminate. In addition, when the baking layer is formed by simultaneously baking a laminated chip having an internal electrode layer 16 and a ceramic layer 14 and a conductive paste applied to the laminated chip, it is preferable that the baking layer is formed by baking a layer to which a ceramic component is added instead of a glass component. The baking layer may be a multi-layered layer.
[0051] When the base electrode layer 32 contains a ceramic component instead of a glass component, it is possible to improve the adhesion between the laminate 12 and the base electrode layer 32. The base electrode layer 32 may contain both a glass component and a ceramic component.
[0052] The ceramic component contained in the base electrode layer 32 may be the same type of ceramic material as that of the ceramic layer 14, or may be a different type of ceramic material. The ceramic component includes at least one selected from the group consisting of BaTiO3, CaTiO3, (Ba,Ca)TiO3, SrTiO3, and CaZrO3.
[0053] The thickness in the length direction z connecting the first end face 12e and the second end face 12f at the center in the height direction x of the first base electrode layer 32a located on the first end face 12e is preferably, for example, from about 2 μm to about 220 μm. The thickness in the length direction z connecting the first end face 12e and the second end face 12f at the center in the height direction x of the second base electrode layer 32b located on the second end face 12f is preferably, for example, from about 2 μm to about 220 μm.
[0054] The thickness in the height direction x connecting the first main surface 12a and the second main surface 12b at the center of the length direction z connecting the first end surface 12e and the second end surface 12f of the first base electrode layer 32a located on a part of the first main surface 12a and the second main surface 12b is preferably, for example, about 3 μm or more and 40 μm or less. The thickness in the height direction x connecting the first main surface 12a and the second main surface 12b at the center of the length direction z connecting the first end surface 12e and the second end surface 12f of the second base electrode layer 32b located on a part of the first main surface 12a and the second main surface 12b is preferably, for example, about 3 μm or more and 40 μm or less.
[0055] The thickness in the width direction y connecting the first side surface 12c and the second side surface 12d at the center of the length direction z connecting the first end surface 12e and the second end surface 12f of the first base electrode layer 32a located at a part of the first side surface 12c and the second side surface 12d is preferably, for example, about 3 μm or more and 40 μm or less. The thickness in the width direction y connecting the first side surface 12c and the second side surface 12d at the center of the length direction z connecting the first end surface 12e and the second end surface 12f of the second base electrode layer 32b located at a part of the first side surface 12c and the second side surface 12d is preferably, for example, about 3 μm or more and 40 μm or less.
[0056] The thin film layer is formed by a thin film forming method such as sputtering or vapor deposition, and is a layer of 1 μm or less in thickness in which metal particles are deposited.
[0057] The conductive resin layer 34 is disposed on the underlying electrode layer 32, and contains a resin component and a metal component. The conductive resin layer 34 is disposed so as to completely cover the underlying electrode layer 32.
[0058] The conductive resin layer 34 includes a first conductive resin layer 34a and a second conductive resin layer 34b. The first conductive resin layer 34a is disposed on the first base electrode layer 32a. The first conductive resin layer 34a is disposed so as to completely cover the first base electrode layer 32a, and an end of the first conductive resin layer 34a is in contact with the laminate 12. The second conductive resin layer 34b is disposed on the second base electrode layer 32b. The second conductive resin layer 34b is disposed so as to completely cover the second base electrode layer 32b, and an end of the second conductive resin layer 34b is in contact with the laminate 12.
[0059] Since the conductive resin layer 34 contains a thermosetting resin, which is a resin component, it is more flexible than the base electrode layer 32 made of, for example, a plating film or a fired product of a metal component and a glass component. Therefore, even if a bending stress is applied to the mounting board and the multilayer ceramic capacitor 10 is subjected to a physical impact or an impact due to a thermal cycle, the conductive resin layer 34 functions as a buffer layer and can prevent the occurrence of cracks in the multilayer ceramic capacitor 10.
[0060] As the thermosetting resin of the conductive resin layer 34, various known thermosetting resins such as epoxy resin, phenoxy resin, phenol resin, urethane resin, silicone resin, polyimide resin, etc. can be used. Among them, epoxy resin, which has excellent heat resistance, moisture resistance, adhesion, etc., is one of the most suitable resins. In addition, it is preferable that the conductive resin layer 34 contains a hardener together with the thermosetting resin. As the hardener, when an epoxy resin is used as the base resin, various known compounds such as phenol-based, amine-based, acid anhydride-based, imidazole-based, active ester-based, and amide-imide-based compounds can be used as the hardener of the epoxy resin.
[0061] The metal component contained in the conductive resin layer 34 is a metal filler. The metal filler can be Ag, Cu, Ni, Sn, Bi, or an alloy containing them. Also, a metal powder with Ag coating on the surface of the metal powder can be used. When using a metal powder with Ag coating on the surface, it is preferable to use Cu, Ni, Sn, Bi, or an alloy powder of these. The reason for using Ag as the metal filler is that Ag has the lowest resistivity among metals, making it suitable as an electrode material, and Ag is a precious metal, so it does not oxidize and has high weather resistance. Also, it is possible to make the base metal cheaper while maintaining the above-mentioned characteristics of Ag.
[0062] The metal filler contained in the conductive resin layer 34 may be Cu or Ni that has been subjected to an anti-oxidation treatment.
[0063] Metal powder having a surface coated with Sn, Ni, or Cu can also be used as the metal filler contained in the conductive resin layer 34. When using metal powder having a surface coated with Sn, Ni, or Cu, it is preferable to use Ag, Cu, Ni, Sn, Bi, or an alloy powder of these metal powders as the metal powder.
[0064] There is no particular limitation on the shape of the metal filler contained in the conductive resin layer 34. The metal filler may be spherical, flat, etc. Also, spherical metal powder and flat metal powder may be mixed.
[0065] There is no particular limitation on the average particle size of the metal filler contained in the conductive resin layer 34. The average particle size of the metal filler may be, for example, about 0.3 μm or more and 10.0 μm or less.
[0066] The average particle size of the metal filler contained in the conductive resin layer 34 can be calculated by using a laser diffraction particle size measurement method based on ISO13320, regardless of the shape of the filler.
[0067] The metal filler contained in the conductive resin layer 34 is mainly responsible for the electrical conductivity of the conductive resin layer 34. Specifically, the metal filler particles come into contact with each other, thereby forming electrical paths inside the conductive resin layer 34.
[0068] The first conductive resin layer 34a has a first end surface side conductive resin layer portion 34a1 located on the first end surface 12e, and a first adjacent conductive resin layer portion 34a2 located extending from an end of the first end surface side conductive resin layer portion 34a1 to a part of the first main surface 12a, a part of the second main surface 12b, a part of the first side surface 12c, and a part of the second side surface 12d. The second conductive resin layer 34b has a second end surface side conductive resin layer portion 34b1 located on the second end surface 12f, and a second adjacent conductive resin layer portion 34b2 located extending from an end of the first end surface side conductive resin layer portion 34a1 to a part of the first main surface 12a, a part of the second main surface 12b, a part of the first side surface 12c, and a part of the second side surface 12d.
[0069] The amount of resin contained in the first adjacent conductive resin layer portion 34a2 is greater than the amount of resin contained in the first end face side conductive resin layer portion 34a1, and the amount of resin contained in the second adjacent conductive resin layer portion 34b2 is greater than the amount of resin contained in the second end face side conductive resin layer portion 34b1. In other words, when the total of the resin components and the metal components in the first end face side conductive resin layer portion 34a1 and the first adjacent conductive resin layer portion 34a2 is taken as 100%, the content ratio of the resin components contained in the first adjacent conductive resin layer portion 34a2 is greater than the content ratio of the resin components contained in the first end face side conductive resin layer portion 34a1, and when the total of the resin components and the metal components in the second end face side conductive resin layer portion 34b1 and the second adjacent conductive resin layer portion 34b2 is taken as 100%, the content ratio of the resin components contained in the second adjacent conductive resin layer portion 34b2 is greater than the content ratio of the resin components contained in the second end face side conductive resin layer portion 34b1. This makes it possible to improve the conductivity in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1, which contain a large amount of metal filler, which is a metal component contained in the conductive resin layer 34, and as a result, to reduce the ESR of the multilayer ceramic capacitor. On the other hand, the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2, which contain a large amount of resin, can be provided with sufficient elasticity, so that when stress due to impact when dropped or deflection stress caused by thermal expansion and contraction of the mounting board due to thermal cycles occurs, the stress transmitted to the mounting board (distortion of the mounting board) is transmitted from the tip of the first adjacent conductive resin layer portion 34a2 to the area between the first base electrode layer 32a and the first adjacent conductive resin layer portion 34a2, In the above manner, peeling can be caused between the second base electrode layer 32b and the second adjacent conductive resin layer portion 34b2, or between the second plating layer 36b and the second adjacent conductive resin layer portion 34b2, starting from the tip of the second adjacent conductive resin layer portion 34b2, and cohesive failure can be caused in the interior of the first adjacent conductive resin layer portion 34a2. Similarly, peeling can be caused between the second base electrode layer 32b and the second adjacent conductive resin layer portion 34b2, or between the second plating layer 36b and the second adjacent conductive resin layer portion 34b2, starting from the tip of the second adjacent conductive resin layer portion 34b2, and cohesive failure can be caused in the interior of the second adjacent conductive resin layer portion 34b2.As a result, it is possible to release stress and suppress the occurrence of cracks in the laminate 12, thereby improving the mechanical strength of the multilayer ceramic capacitor 10. As described above, the present invention makes it possible to effectively achieve both the improvement of the mechanical strength of the multilayer ceramic capacitor 10 and the ESR characteristics in the trade-off relationship between these characteristics.
[0070] The content ratio of the resin component in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 is 10% or more and 60% or less, when the total of the resin component and the metal component is 100%. As a result, while ensuring conductivity and reducing ESR in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1, when stress due to impact when dropped or flexural stress caused by thermal expansion and contraction of the mounting substrate due to thermal cycles occurs, the stress transmitted to the mounting substrate (distortion of the mounting substrate) can be caused to peel off between the first base electrode layer 32a and the first adjacent conductive resin layer portion 34a2, or between the first plating layer 36a and the first adjacent conductive resin layer portion 34a2, starting from the tip of the first adjacent conductive resin layer portion 34a2. Similarly, the tip of the second adjacent conductive resin layer portion 34b2 can be caused to peel off between the second base electrode layer 32b and the second adjacent conductive resin layer portion 34b2, or between the second plating layer 36b and the second adjacent conductive resin layer portion 34b2. This allows stress to be released, making it possible to prevent the laminate 12 from cracking.
[0071] When the content ratio of the resin component in the first end surface side conductive resin layer portion 34a1 and the second end surface side conductive resin layer portion 34b1 is less than 10% when the sum of the resin component and the metal component is 100%, the ratio of the metal component in the first end surface side conductive resin layer portion 34a1 and the second end surface side conductive resin layer portion 34b1 increases, and the amount of resin that should be present around the metal filler constituting the metal component decreases. Here, the conductive resin layer 34 generally makes the metal filler particles contact each other by pulling the metal filler particles by shrinking the resin when the conductive resin layer 34 is cured. However, as described above, when the content ratio of the resin component decreases, the shrinkage becomes small, and the metal filler particles cannot be sufficiently brought into contact with each other, resulting in a state in which voids are generated between the metal filler particles. This deteriorates the ESR.
[0072] Furthermore, when the content ratio of the resin component in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 is more than 60% when the sum of the resin component and the metal component is 100%, the high content ratio of the resin component in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 prevents contact between the metal fillers that make up the metal component and increases the distance between the metal fillers, thereby deteriorating the ESR.
[0073] The resin component content in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 can be measured on a cross section as follows: First, polishing is started from the first side face 12c or the second side face 12d of the multilayer ceramic capacitor 10, and polished to a position that is 1 / 2W in the width direction y connecting the first side face 12c and the second side face 12d. On the LT surface, the center in the height direction x of the first end face side conductive resin layer portion 34a1 on the first end face 12e side or the second end face side conductive resin layer portion 34b1 on the second end face 12f side is confirmed. Alternatively, polishing is started from the first main surface 12a or the second main surface 12b of the multilayer ceramic capacitor 10, and the LW surface is polished to a position that is 1 / 2T in the height direction x connecting the first main surface 12a and the second main surface 12b, and the center of the width direction y of the first end face side conductive resin layer portion 34a1 on the first end face 12e side or the second end face side conductive resin layer portion 34b1 on the second end face 12f side is confirmed. Next, using a scanning electron microscope (SEM), a backscattered electron image is observed and photographed at an acceleration voltage of 5 kV and a magnification of 1000 times so that the thermosetting resin can be distinguished from other parts (metal components (metal filler), voids). After that, the photographed image is binarized by image analysis software to separate the thermosetting resin from other parts, and the content ratio of the resin component in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 can be obtained.
[0074] The content ratio of the metal component in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 is preferably 40% or more and 90% or less when the total of the resin component and the metal component is taken as 100%. This makes it possible to improve the conductivity of the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1, which contain a large amount of metal filler constituting the metal component, and as a result, the ESR of the multilayer ceramic capacitor 10 is reduced.
[0075] If the content ratio of the metal component in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 is less than 40% when the sum of the resin component and the metal component is 100%, the high content ratio of the resin component in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 may prevent contact between the metal fillers that make up the metal component and increase the distance between the metal fillers, which may result in a deterioration of the ESR.
[0076] When the content ratio of the metal component in the first end face side conductive resin layer part 34a1 and the second end face side conductive resin layer part 34b1 is more than 90% when the total of the resin component and the metal component is 100%, the content ratio of the metal component in the first end face side conductive resin layer part 34a1 and the second end face side conductive resin layer part 34b1 increases, and the amount of resin that should be present around the metal filler constituting the metal component decreases. Here, the conductive resin layer 34 generally makes the metal filler particles contact each other by pulling the metal filler particles by shrinking the resin when the conductive resin layer 34 is cured. However, as described above, when the content ratio of the resin component decreases, the shrinkage becomes small, and the metal filler particles cannot be sufficiently brought into contact with each other, resulting in a state in which voids are generated between the metal filler particles. This may cause the ESR to deteriorate.
[0077] The content ratio of the metal component in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 can be measured on a cross section as follows: First, polishing is started from the first side face 12c or the second side face 12d of the multilayer ceramic capacitor 10, and the center in the height direction x of the first end face side conductive resin layer portion 34a1 on the first end face 12e side or the second end face side conductive resin layer portion 34b1 on the second end face 12f side is confirmed on the LT surface polished to a position that is 1 / 2W in the width direction y connecting the first side face 12c and the second side face 12d. Alternatively, polishing is started from the first main surface 12a or the second main surface 12b of the multilayer ceramic capacitor 10, and the LW surface is polished to a position that is 1 / 2T in the height direction x connecting the first main surface 12a and the second main surface 12b, and the center of the width direction y of the first end face side conductive resin layer portion 34a1 on the first end face 12e side or the second end face side conductive resin layer portion 34b1 on the second end face 12f side is confirmed. Next, using a scanning electron microscope (SEM), a backscattered electron image is observed and photographed at an acceleration voltage of 5 kV and a magnification of 1000 times so that the thermosetting resin and other parts (metal components (metal filler), voids) can be distinguished. After that, the photographed image is binarized by image analysis software to separate the thermosetting resin from the other parts, and the content ratio of the metal components in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 can be obtained.
[0078] The content ratio of the resin component in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 is preferably 40% or more and 60% or less when the total of the resin component and the metal component is taken as 100%. This makes it possible to provide sufficient elasticity in the portions where the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2, which are susceptible to stress, are arranged. Therefore, when stress due to impact when dropped or deflection stress caused by thermal expansion of the mounting board due to thermal cycles occurs, the stress (mounting board distortion) transmitted to the mounting board can be peeled off between the first base electrode layer 32a and the first adjacent conductive resin layer portion 34a2, or between the first plating layer 36a and the first adjacent conductive resin layer portion 34a2, starting from the tip of the portion where the first adjacent conductive resin layer portion 34a2 is arranged. Similarly, peeling can be caused between the second base electrode layer 32b and the second adjacent conductive resin layer portion 34b2, or between the second plating layer 36b and the second adjacent conductive resin layer portion 34b2, starting from the tip of the portion where the second adjacent conductive resin layer portion 34b2 is arranged. This allows stress to be released and makes it possible to prevent cracks from occurring in the laminate 12, thereby improving the mechanical strength of the multilayer ceramic capacitor 10.
[0079] When the content ratio of the resin component in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 is less than 40% when the total of the resin component and the metal component is taken as 100%, the content ratio of the metal component in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 becomes high. When comparing the elastic modulus and hardness of the metal filler constituting the metal component with that of the resin, the metal filler has a higher value. Therefore, by increasing the ratio of metal filler contained in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2, the entire conductive resin layer 34 becomes strong and hard, and even when stress due to impact when dropped or deflection stress caused by thermal expansion and contraction of the mounting substrate due to thermal cycles occurs, the stress transmitted to the mounting substrate (distortion of the mounting substrate) cannot be peeled off from the tip of the portion where the first adjacent conductive resin layer portion 34a2 is arranged between the first base electrode layer 32a and the first adjacent conductive resin layer portion 34a2, or between the first plating layer 36a and the first adjacent conductive resin layer portion 34a2. Similarly, the tip of the portion where the second adjacent conductive resin layer portion 34b2 is arranged cannot be peeled off from the tip of the portion where the second adjacent conductive resin layer portion 34b2 is arranged between the second base electrode layer 32b and the second adjacent conductive resin layer portion 34b2, or between the second plating layer 36b and the second adjacent conductive resin layer portion 34b2. Therefore, the laminate 12 may crack.
[0080] When the content ratio of the resin component in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 is more than 90% when the sum of the resin component and the metal component is 100%, the amount of resin in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 increases, so that the metal filler exposed on the surface of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 decreases. When the amount of metal filler exposed on the surface of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 decreases, the starting point of the plating growth of the plating layer 36 formed on the surface of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 decreases, so that the plating formation is hindered. When the plating formation is hindered, there are parts where the plating is not formed, and the plating layer becomes discontinuous and has multiple missing parts. Since stress tends to concentrate in the multiple defects, when stress due to impact when dropped or deflection stress caused by thermal expansion and contraction of the mounting board due to thermal cycle occurs, stress is also applied to the defects, and the first base electrode layer 32a and the first adjacent conductive resin layer portion 34a2, or the first plating layer 36a and the first adjacent conductive resin layer portion 34a2 cannot be sufficiently peeled from the tip of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2, and similarly, the second base electrode layer 32b and the second adjacent conductive resin layer portion 34b2, or the second plating layer 36b and the second adjacent conductive resin layer portion 34b2 cannot be sufficiently peeled from the tip of the portion where the second adjacent conductive resin layer portion 34b2 is arranged. Therefore, cracks may occur in the laminate 12.
[0081] The resin component content ratios in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 can be measured on a cross section as follows: First, polishing is started from the first side surface 12c or the second side surface 12d of the multilayer ceramic capacitor 10, and polished to a position that is 1 / 2W in the width direction y connecting the first side surface 12c and the second side surface 12d, and the center portion in the length direction z of the first adjacent conductive resin layer portion 34a2 on the first main surface 12a side or the second main surface 12b side or the second adjacent conductive resin layer portion 34b2 on the first main surface 12a side or the second main surface 12b side is confirmed on the LT surface. Alternatively, polishing is started from the first main surface 12a or the second main surface 12b of the multilayer ceramic capacitor 10, and the LW surface is polished to a position that is 1 / 2T of the height direction x connecting the first main surface 12a and the second main surface 12b, and the center of the length direction z of the first adjacent conductive resin layer portion 34a2 on the first side surface 12c side or the second side surface 12d side or the second adjacent conductive resin layer portion 34b2 on the first side surface 12c side or the second side surface 12d side is confirmed. Next, using a scanning electron microscope (SEM), a backscattered electron image is observed and photographed at an acceleration voltage of 5 kV and a magnification of 1000 times so that the thermosetting resin and other parts (metal components (metal filler), voids) can be distinguished. After that, the photographed image is binarized by image analysis software into the thermosetting resin and other parts, and the content ratio of the resin component in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 can be obtained.
[0082] The content ratio of the metal component in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 is preferably 10% or more and 60% or less when the total of the resin component and the metal component is taken as 100%. This ensures electrical continuity, and when stress due to impact when dropped or deflection stress caused by thermal expansion and contraction of the mounting board due to thermal cycle occurs, the stress (distortion of the mounting board) transmitted to the mounting board can be peeled off between the first base electrode layer 32a and the first adjacent conductive resin layer portion 34a2, or between the first plating layer 36a and the first adjacent conductive resin layer portion 34a2, starting from the tip of the portion where the first adjacent conductive resin layer portion 34a2 is arranged, and similarly, the second base electrode layer 32b and the second adjacent conductive resin layer portion 34b2, or between the second plating layer 36b and the second adjacent conductive resin layer portion 34b2, starting from the tip of the portion where the second adjacent conductive resin layer portion 34b2 is arranged. As a result, the stress acting on the laminate 12 can be released by forming the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2.
[0083] When the content ratio of the metal component in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 is less than 10% when the total of the resin component and the metal component is 100%, the amount of resin in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 increases, so that the metal filler exposed on the surface of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 decreases. When the amount of metal filler exposed on the surface of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 decreases, the starting point of the plating growth of the plating layer 36 formed on the surface of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 decreases, so that the plating formation is hindered. When the plating formation is hindered, there are parts where the plating is not formed, and the plating layer becomes discontinuous and has multiple missing parts. Since stress tends to concentrate in the multiple defects, when stress due to impact when dropped or deflection stress caused by thermal expansion and contraction of the mounting board due to thermal cycle occurs, stress is also applied to the defects, and the first base electrode layer 32a and the first adjacent conductive resin layer portion 34a2, or the first plating layer 36a and the first adjacent conductive resin layer portion 34a2 cannot be sufficiently peeled from the tip of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2, and similarly, the second base electrode layer 32b and the second adjacent conductive resin layer portion 34b2, or the second plating layer 36b and the second adjacent conductive resin layer portion 34b2 cannot be sufficiently peeled from the tip of the portion where the second adjacent conductive resin layer portion 34b2 is arranged. Therefore, cracks may occur in the laminate 12.
[0084] When the total of the resin component and the metal component is taken as 100%, the content ratio of the metal component in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 is more than 60%, the content ratio of the metal component in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 is high. When the elastic modulus and hardness of the metal filler constituting the metal component are compared with that of the resin, the metal filler has a higher value. Therefore, by increasing the ratio of metal filler contained in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2, the entire conductive resin layer 34 becomes strong and hard, and even when stress due to impact when dropped or deflection stress caused by thermal expansion and contraction of the mounting substrate due to thermal cycles occurs, the stress transmitted to the mounting substrate (distortion of the mounting substrate) cannot be peeled off from the tip of the portion where the first adjacent conductive resin layer portion 34a2 is arranged between the first base electrode layer 32a and the first adjacent conductive resin layer portion 34a2, or between the first plating layer 36a and the first adjacent conductive resin layer portion 34a2. Similarly, the tip of the portion where the second adjacent conductive resin layer portion 34b2 is arranged cannot be peeled off from the tip of the portion where the second adjacent conductive resin layer portion 34b2 is arranged between the second base electrode layer 32b and the second adjacent conductive resin layer portion 34b2, or between the second plating layer 36b and the second adjacent conductive resin layer portion 34b2. Therefore, the laminate 12 may crack.
[0085] The content ratio of the metal component in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 can be measured on a cross section as follows: First, polishing is started from the first side surface 12c or the second side surface 12d of the multilayer ceramic capacitor 10, and polished to a position that is 1 / 2W in the width direction y connecting the first side surface 12c and the second side surface 12d, and the center in the height direction x of the first adjacent conductive resin layer portion 34a2 on the first main surface 12a side or the second main surface 12b side or the second adjacent conductive resin layer portion 34b2 on the first main surface 12a side or the second main surface 12b side is confirmed on the LT surface. Alternatively, polishing is started from the first main surface 12a or the second main surface 12b of the multilayer ceramic capacitor 10, and the LW surface is polished to a position that is 1 / 2T of the height direction x connecting the first main surface 12a and the second main surface 12b, and the center of the length direction z of the first adjacent conductive resin layer portion 34a2 on the first side surface 12c side or the second side surface 12d side or the second adjacent conductive resin layer portion 34b2 on the first side surface 12c side or the second side surface 12d side is confirmed. Next, using a scanning electron microscope (SEM), a backscattered electron image is observed and photographed at an acceleration voltage of 5 kV and a magnification of 1000 times so that the thermosetting resin and other parts (metal components (metal filler), voids) can be distinguished. After that, the photographed image is binarized by image analysis software to separate the thermosetting resin from the other parts, and the content ratio of the metal components in the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 can be obtained.
[0086] The thickness of the conductive resin layer 34 located at the center in the height direction x of the laminate 12, which is located at the first end face 12e and the second end face 12f, is preferably, for example, about 20.0 μm or more and 150.0 μm or less.
[0087] Furthermore, when a conductive resin layer is provided on the first main surface 12a, the second main surface 12b, the first side surface 12c, and the second side surface 12d, the thickness of the conductive resin layer 34 at the central portions in the longitudinal direction z of the conductive resin layer located on the first main surface 12a, the second main surface 12b, the first side surface 12c, and the second side surface 12d is preferably, for example, approximately 5.0 μm or more and 40.0 μm or less.
[0088] It is preferable that the conductivity (resistance) of the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 is 5 Ω·cm or more and 25 Ω·cm or less, and the conductivity (resistance) of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 is 20 Ω·cm or more and 150 Ω·cm or less, thereby reducing the ESR of the multilayer ceramic capacitor 10.
[0089] It is preferable that the indentation elastic modulus of the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 is 15 GPa or more and 21 GPa or less, and the indentation elastic modulus of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 is 12 GPa or more and 15 GPa or less. This makes it possible to release stress on the laminate 12 and to suppress the occurrence of cracks in the laminate 12, thereby improving the mechanical strength of the multilayer ceramic capacitor 10.
[0090] It is preferable that the storage modulus of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 is 6 GPa or more and 8 GPa or less, and the storage modulus of the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 is 8 GPa or more and 10 GPa or less. This makes it possible to release stress on the laminate 12 and suppress the occurrence of cracks in the laminate 12, thereby improving the mechanical strength of the multilayer ceramic capacitor 10.
[0091] It is preferable that the loss modulus of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 is 0.2 GPa or more and 0.4 GPa or less, and the loss modulus of the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 is 0.4 GPa or more and 0.5 GPa or less. This makes it possible to release stress on the laminate 12 and suppress the occurrence of cracks in the laminate 12, thereby improving the mechanical strength of the multilayer ceramic capacitor 10.
[0092] It is preferable that the hardness of the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2 is 0.1 GPa or more and 0.3 GPa or less, and the hardness of the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 is 0.2 GPa or more and 0.7 GPa or less. This makes it possible to release stress on the laminate 12 and suppress the occurrence of cracks in the laminate 12, thereby improving the mechanical strength of the multilayer ceramic capacitor 10.
[0093] Next, the first plating layer 36a and the second plating layer 36b, which are the plating layer 36 disposed on the base electrode layer 32, will be described with reference to Figures 2 and 3. The first plating layer 36a and the second plating layer 36b include at least one selected from, for example, Cu, Ni, Sn, Ag, Pd, an Ag-Pd alloy, Au, and the like.
[0094] The first plating layer 36a is disposed so as to completely cover the first conductive resin layer 34a, and the second plating layer 36b is disposed so as to completely cover the second conductive resin layer 34b.
[0095] The first plating layer 36a and the second plating layer 36b may be formed of multiple layers. In this case, the plating layer 36 preferably has a two-layer structure of a lower plating layer (Ni plating layer) formed on the conductive resin layer 34 by Ni plating, and an upper plating layer (Sn plating layer) formed on the lower plating layer by Sn plating. That is, the first plating layer 36a has a first lower plating layer and a first upper plating layer located on the surface of the first lower plating layer. The second plating layer 36b has a second lower plating layer and a second upper plating layer located on the surface of the second lower plating layer.
[0096] The lower plating layer made of Ni plating is used to prevent the base electrode layer 32 and the conductive resin layer 34 from being eroded by solder when mounting the multilayer ceramic capacitor 10, and the upper plating layer made of Sn plating is used to improve the wettability of the solder when mounting the multilayer ceramic capacitor 10, thereby facilitating mounting. The thickness of each plating layer is preferably 1.0 μm or more and 15.0 μm or less.
[0097] The dimension of the multilayer ceramic capacitor 10 including the laminate 12, the first external electrode 30a, and the second external electrode 30b in the length direction z is defined as dimension L, the dimension of the multilayer ceramic capacitor 10 including the laminate 12, the first external electrode 30a, and the second external electrode 30b in the height direction x is defined as dimension T, and the dimension of the multilayer ceramic capacitor 10 including the laminate 12, the first external electrode 30a, and the second external electrode 30b in the width direction y is defined as dimension W. The dimensions of the multilayer ceramic capacitor 10 are such that the L dimension in the length direction z is 0.2 mm or more and 10.0 mm or less, the W dimension in the width direction y is 0.1 mm or more and 10.0 mm or less, and the T dimension in the height direction x is 0.1 mm or more and 10.0 mm or less. The dimensions of the multilayer ceramic capacitor 10 can be measured using a microscope.
[0098] 1, when the sum of the resin components and the metal components in the first end face side conductive resin layer portion 34a1 and the first adjacent conductive resin layer portion 34a2 is taken as 100%, the content ratio of the resin components in the first adjacent conductive resin layer portion 34a2 is higher than the content ratio of the resin components in the first end face side conductive resin layer portion 34a1, and when the sum of the resin components and the metal components in the second end face side conductive resin layer portion 34b1 and the second adjacent conductive resin layer portion 34b2 is taken as 100%, the content ratio of the resin components in the second adjacent conductive resin layer portion 34b2 is higher than the content ratio of the resin components in the second end face side conductive resin layer portion 34b1. Also, when the sum of the resin components and the metal components in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 is taken as 100%, the content ratio of the resin components in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1 is 10% or more and 60% or less. As a result, when the total of the resin component and the metal component is taken as 100%, the content ratio of the resin component in the first end face side conductive resin layer portion 34a1 and the second end face side conductive resin layer portion 34b1, which contain a large amount of metal filler, is 10% or more and 60% or less, so that it is possible to improve the conductivity and, as a result, to reduce the ESR of the multilayer ceramic capacitor. On the other hand, the first adjacent conductive resin layer portion 34a2 and the second adjacent conductive resin layer portion 34b2, which contain a large amount of resin, can have sufficient elasticity. Therefore, when stress due to impact when dropped or deflection stress caused by thermal expansion and contraction of the mounting substrate due to thermal cycle occurs, the stress (distortion of the mounting substrate) transmitted to the mounting substrate is transmitted from the tip of the first adjacent conductive resin layer portion 34a2 to the first base electrode layer 32a and the first adjacent conductive resin layer portion 34a2, and the first base electrode layer 32a and the first adjacent conductive resin layer portion 34b2 are transmitted to the first base electrode layer 32a and the first adjacent conductive resin layer portion 34b2, starting from the tip of the first adjacent conductive resin layer portion 34a2. In the above manner, peeling can be caused between the second base electrode layer 32b and the second adjacent conductive resin layer portion 34b2, or between the second plating layer 36b and the second adjacent conductive resin layer portion 34b2, starting from the tip of the second adjacent conductive resin layer portion 34b2, and cohesive failure can be caused in the interior of the first adjacent conductive resin layer portion 34a2. Similarly, peeling can be caused between the second base electrode layer 32b and the second adjacent conductive resin layer portion 34b2, or between the second plating layer 36b and the second adjacent conductive resin layer portion 34b2, starting from the tip of the second adjacent conductive resin layer portion 34b2, and cohesive failure can be caused in the interior of the second adjacent conductive resin layer portion 34b2.As a result, it is possible to release stress and suppress the occurrence of cracks in the laminate 12, thereby improving the mechanical strength of the multilayer ceramic capacitor 10. As described above, the present invention makes it possible to effectively achieve both the improvement of the mechanical strength of the multilayer ceramic capacitor 10 and the ESR characteristics in the trade-off relationship between these characteristics.
[0099] 2. Manufacturing method of multilayer ceramic capacitors Next, a method for manufacturing the multilayer ceramic capacitor will be described.
[0100] First, a dielectric sheet for the ceramic layer and a conductive paste for the internal electrode layer are prepared. The dielectric sheet and the conductive paste for the internal electrode layer contain a binder and a solvent. The binder and the solvent may be known.
[0101] Then, the conductive paste for the internal electrode layers is printed in a predetermined pattern on the dielectric sheet by, for example, screen printing, gravure printing, etc. In this way, a dielectric sheet on which the pattern of the first internal electrode layer is formed, and a dielectric sheet on which the pattern of the second internal electrode layer is formed are prepared.
[0102] Regarding the dielectric sheets, outer layer dielectric sheets on which no internal electrode layer patterns are printed are also prepared.
[0103] Next, a predetermined number of dielectric sheets for outer layers, on which the pattern of the internal electrode layer is not printed, are laminated to form a portion that will become the second outer layer portion on the second main surface side. Then, a dielectric sheet on which the pattern of the first internal electrode layer is printed and a dielectric sheet on which the pattern of the second internal electrode layer is printed are laminated in order on the portion that will become the second outer layer portion so as to form the structure of the present invention, to form a portion that will become the effective layer portion. A predetermined number of dielectric sheets for outer layers, on which the pattern of the internal electrode layer is not printed, are laminated on the portion that will become the effective layer portion to form a portion that will become the first outer layer portion on the first main surface side.
[0104] Next, the laminated sheets are pressed in the lamination direction by means of a hydrostatic press or the like to produce a laminated block.
[0105] The laminated block is then cut to a predetermined size to obtain laminated chips. At this time, corners and edges of the laminated chips may be rounded by barrel polishing or the like.
[0106] Next, the laminated chip is fired to produce the laminate 12. The firing temperature depends on the materials of the ceramic layers, which are dielectric layers, and the internal electrode layers, but is preferably 900° C. or higher and 1400° C. or lower.
[0107] Next, a conductive paste that will become the base electrode layer is applied to the first end face and the second end face of the laminate to form the base electrode layer. When forming a baked layer as the base electrode layer, a conductive paste containing a glass component and a metal is applied by a method such as dipping, and then a baking process is performed to form the base electrode layer. The temperature of the baking process at this time is preferably 700°C or more and 950°C or less.
[0108] When the base electrode layer is formed of a baked layer, the baked layer may contain a ceramic component. In this case, the ceramic component may be contained instead of the glass component, or both may be contained.
[0109] The ceramic component is preferably, for example, the same type of ceramic material as the laminate. When the ceramic component is included in the baking layer, it is preferable to apply a conductive paste to the laminated chip before firing, and simultaneously bake (fire) the laminated chip before firing and the conductive paste applied to the laminated chip before firing to form a laminate with a baked layer. The temperature (firing temperature) of the baking process at this time is preferably 900°C or higher and 1400°C or lower.
[0110] Next, a conductive resin layer is formed on the base electrode layer, with the end face side conductive resin layer portion and the adjacent conductive resin layer portion being formed by coating separately.
[0111] The end surface side conductive resin layer portion is formed by the following method. First, the laminate is arranged on a back plate with the first end surface side or the second end surface side facing upward, and the first conductive resin paste for the end surface side conductive resin layer portion is applied only to the portion where the end surface side conductive resin layer portion is to be formed. The amount of metal filler contained in the first conductive resin paste is preferably 35 vol% or more and 95 vol% or less with respect to the resin component. Also, the amount of resin component contained in the first conductive resin paste is preferably 5 vol% or more and 65 vol% or less with respect to the metal filler. Then, a heat treatment is performed at a temperature of 200°C or more and 550°C or less to harden the first conductive resin paste. The atmosphere during the heat treatment at this time is preferably an N2 atmosphere. Also, in order to prevent the resin from scattering and to prevent the oxidation of various metal components, the oxygen concentration is preferably suppressed to 100 ppm or less.
[0112] Next, the adjacent conductive resin layer part is formed by the following method. First, the first main surface side, the second main surface side, the first side surface side, and the second side surface side of the laminate are arranged on an alignment plate with each side facing upward, and masking is performed so that the second conductive resin paste for the adjacent conductive resin layer part can be applied only to the part where the second conductive resin paste for the adjacent conductive resin layer part is to be formed, and the second conductive resin paste for the adjacent conductive resin layer part is applied by using a screen printing method. The amount of the metal filler contained in the second conductive resin paste is preferably 5 vol% or more and 65 vol% or less with respect to the resin component. Also, the amount of the resin component contained in the second conductive resin paste is preferably 50 vol% or more and 95 vol% or less with respect to the metal filler. Then, a heat treatment is performed at a temperature of 200°C or more and 550°C or less to harden the second conductive resin paste. The atmosphere during the heat treatment at this time is preferably an N2 atmosphere. In order to prevent the resin from scattering and the various metal components from oxidizing, it is preferable to keep the oxygen concentration at 100 ppm or less.
[0113] In the present invention, the metal filler and resin amount in the end face side conductive resin layer portion and the adjacent conductive resin layer portion can be controlled by adjusting the heat treatment temperature of the end face side conductive resin layer portion and the adjacent conductive resin layer portion, and the amount of metal filler and resin amount contained in the first conductive resin paste and the second conductive resin paste used when forming the end face side conductive resin layer portion and the adjacent conductive resin layer portion.
[0114] Next, a plating layer is formed on the surface of the base electrode layer. More specifically, a Ni plating layer is formed on the base electrode layer, and a Sn plating layer is formed on the Ni plating layer. Electroless plating is used for the plating process. The conductive resin layer has a low content of metal components, making it difficult to conduct electricity. Therefore, the plating layer is formed by electrolytic plating. As the plating method, barrel plating is preferably used.
[0115] In the manner described above, the multilayer ceramic capacitor 10 according to the present embodiment is manufactured.
[0116] 3. Experimental Example 1 According to the above-mentioned manufacturing method, a multilayer ceramic capacitor was fabricated as a sample of the multilayer ceramic electronic component, and was evaluated by measuring the ESR and checking for the presence or absence of cracks in the laminate by a substrate bending test.
[0117] (a) Specifications of the samples in the examples As an example, a multilayer ceramic capacitor having the structure shown in FIGS. 1 to 4 and the following specifications was prepared.
[0118] · Dimensions of multilayer ceramic capacitor (design value): L×W×T=3.2mm×2.5mm×2.5mm · Main component material of ceramic layer: BaTiO3 ·Capacity: 1nF Rated voltage: 50V Internal electrode layer material: Ni External electrode layer specifications - Specifications of the base electrode layer · Base electrode layer: A baked layer containing metal and glass components ·Metal component: Cu -Thickness of the base electrode layer Thickness in the length direction z at the center in the height direction x of the base electrode layer located at the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 30 μm Thickness in the height direction x connecting the first and second principal surfaces at the center in the length direction z of the base electrode layer located on the first and second principal surfaces in the cross section of the laminate at the 1 / 2W position (thickness of the base electrode layer at the center part in dimension e): 5 μm Thickness in the width direction y connecting the first side surface and the second side surface at the center in the length direction z of the base electrode layer located on the first side surface and the second side surface in the cross section of the laminate at the 1 / 2T position (thickness of the base electrode layer at the center part of dimension e): 5 μm -Conductive resin layer specifications Conductive resin layer on the end face: Metal filler: Ag Resin component: Epoxy type Heat curing temperature: 230℃ Thickness in the length direction z at the center in the height direction x of the end face side conductive resin layer portion located at the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 30 μm The ratio of metal filler and resin content: Metal filler: Resin = 70:30 Adjacent conductive resin layer: Metal filler: Ag Resin component: Epoxy type Heat curing temperature: 230℃ Thickness in the length direction z at the center in the height direction x of the end face side conductive resin layer portion located at the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 10 μm The ratio of metal filler and resin content: Metal filler: Resin = 40:60 · Specifications of plating layer: Formed in two layers, with a Ni plating layer formed on the base electrode layer and a Sn plating layer formed on the Ni plating layer. -Thickness of Ni plating layer Thickness in the length direction z at the center in the height direction x of the Ni plating layer located on the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 3 μm Thickness at the center in the longitudinal direction z of the Ni plating layer located on the first principal surface, the second principal surface, and the first side surface, and the second side surface: 3 μm ·Thickness of Sn plating layer Thickness in the length direction z at the center in the height direction x of the Ni plating layer located on the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 4 μm Thickness at the center in the longitudinal direction z of the Ni plating layer located on the first principal surface, the second principal surface, and the first side surface, and the second side surface: 4 μm
[0119] (b) Specifications of the sample of Comparative Example 1 A multilayer ceramic capacitor with the following specifications was prepared as Comparative Example 1. That is, in the multilayer ceramic capacitor of Comparative Example 1, the amount of resin contained in the end face side conductive resin layer portion was 60 vol %, and the amount of resin contained in the adjacent conductive resin layer portion was 60 vol %. Other specifications are as follows:
[0120] · Dimensions of multilayer ceramic capacitor (design value): L×W×T=3.2mm×2.5mm×2.5mm · Main component material of ceramic layer: BaTiO3 ·Capacity: 1nF Rated voltage: 50V Internal electrode layer material: Ni External electrode layer specifications - Specifications of the base electrode layer · Base electrode layer: A baked layer containing metal and glass components ·Metal component: Cu -Thickness of the base electrode layer Thickness in the length direction z at the center in the height direction x of the base electrode layer located at the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 30 μm Thickness in the height direction x connecting the first and second principal surfaces at the center in the length direction z of the base electrode layer located on the first and second principal surfaces in the cross section of the laminate at the 1 / 2W position (thickness of the base electrode layer at the center part in dimension e): 5 μm Thickness in the width direction y connecting the first side surface and the second side surface at the center in the length direction z of the base electrode layer located on the first side surface and the second side surface in the cross section of the laminate at the 1 / 2T position (thickness of the base electrode layer at the center part of dimension e): 5 μm -Conductive resin layer specifications Conductive resin layer on the end face: Metal filler: Ag Resin component: Epoxy type Heat curing temperature: 230℃ Thickness in the length direction z at the center in the height direction x of the end face side conductive resin layer portion located at the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 30 μm The ratio of metal filler and resin content: Metal filler: Resin = 40:60 Adjacent conductive resin layer: Metal filler: Ag Resin component: Epoxy type Heat curing temperature: 230℃ Thickness in the length direction z at the center in the height direction x of the end face side conductive resin layer portion located at the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 10 μm The ratio of metal filler and resin content: Metal filler: Resin = 40:60 · Specifications of plating layer: Formed in two layers, with a Ni plating layer formed on the base electrode layer and a Sn plating layer formed on the Ni plating layer. -Thickness of Ni plating layer Thickness in the length direction z at the center in the height direction x of the Ni plating layer located on the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 3 μm Thickness at the center in the longitudinal direction z of the Ni plating layer located on the first principal surface, the second principal surface, and the first side surface, and the second side surface: 3 μm ·Thickness of Sn plating layer Thickness in the length direction z at the center in the height direction x of the Ni plating layer located on the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 4 μm Thickness at the center in the longitudinal direction z of the Ni plating layer located on the first principal surface, the second principal surface, and the first side surface, and the second side surface: 4 μm
[0121] (c) Specifications of the sample of Comparative Example 2 A multilayer ceramic capacitor having the following specifications was prepared as Comparative Example 2. A multilayer ceramic capacitor having the following specifications was prepared as Comparative Example 2. That is, the multilayer ceramic capacitor of Comparative Example 1 has a resin amount of 60 vol% in the end face side conductive resin layer portion and a resin amount of 30 vol% in the adjacent conductive resin layer portion. Other specifications are as follows.
[0122] · Dimensions of multilayer ceramic capacitor (design value): L×W×T=3.2mm×2.5mm×2.5mm · Main component material of ceramic layer: BaTiO3 ·Capacity: 1nF Rated voltage: 50V Internal electrode layer material: Ni External electrode layer specifications - Specifications of the base electrode layer · Base electrode layer: A baked layer containing metal and glass components ·Metal component: Cu -Thickness of the base electrode layer Thickness in the length direction z at the center in the height direction x of the base electrode layer located at the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 30 μm Thickness in the height direction x connecting the first and second principal surfaces at the center in the length direction z of the base electrode layer located on the first and second principal surfaces in the cross section of the laminate at the 1 / 2W position (thickness of the base electrode layer at the center part in dimension e): 5 μm Thickness in the width direction y connecting the first side surface and the second side surface at the center in the length direction z of the base electrode layer located on the first side surface and the second side surface in the cross section of the laminate at the 1 / 2T position (thickness of the base electrode layer at the center part of dimension e): 5 μm -Conductive resin layer specifications Conductive resin layer on the end face: Metal filler: Ag Resin component: Epoxy type Heat curing temperature: 230℃ Thickness in the length direction z at the center in the height direction x of the end face side conductive resin layer portion located at the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 30 μm The ratio of metal filler and resin content: Metal filler: Resin = 40:60 Adjacent conductive resin layer: Metal filler: Ag Resin component: Epoxy type Heat curing temperature: 230℃ Thickness in the length direction z at the center in the height direction x of the end face side conductive resin layer portion located at the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 10 μm The ratio of metal filler and resin content: Metal filler: Resin = 70:30 · Specifications of plating layer: Formed in two layers, with a Ni plating layer formed on the base electrode layer and a Sn plating layer formed on the Ni plating layer. -Thickness of Ni plating layer Thickness in the length direction z at the center in the height direction x of the Ni plating layer located on the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 3 μm Thickness at the center in the longitudinal direction z of the Ni plating layer located on the first principal surface, the second principal surface, and the first side surface, and the second side surface: 3 μm ·Thickness of Sn plating layer Thickness in the length direction z at the center in the height direction x of the Ni plating layer located on the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 4 μm Thickness at the center in the longitudinal direction z of the Ni plating layer located on the first principal surface, the second principal surface, and the first side surface, and the second side surface: 4 μm
[0123] (d) Specifications of the sample of Comparative Example 3 A multilayer ceramic capacitor having the following specifications was prepared as Comparative Example 3. That is, a multilayer ceramic capacitor was prepared in which the conductive resin layer itself was not provided on the external electrodes. The other specifications were as follows.
[0124] · Dimensions of multilayer ceramic capacitor (design value): L×W×T=3.2mm×2.5mm×2.5mm · Main component material of ceramic layer: BaTiO3 ·Capacity: 1nF Rated voltage: 50V Internal electrode layer material: Ni External electrode layer specifications - Specifications of the base electrode layer · Base electrode layer: A baked layer containing metal and glass components ·Metal component: Cu -Thickness of the base electrode layer Thickness in the length direction z at the center in the height direction x of the base electrode layer located at the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 80 μm Thickness in the height direction x connecting the first and second principal surfaces at the center in the length direction z of the base electrode layer located on the first and second principal surfaces in the cross section of the laminate at the 1 / 2W position (thickness of the base electrode layer at the center part in dimension e): 5 μm Thickness in the width direction y connecting the first side surface and the second side surface at the center in the length direction z of the base electrode layer located on the first side surface and the second side surface in the cross section of the laminate at the 1 / 2T position (thickness of the base electrode layer at the center part of dimension e): 5 μm · Specifications of plating layer: Formed in two layers, with a Ni plating layer formed on the base electrode layer and a Sn plating layer formed on the Ni plating layer. -Thickness of Ni plating layer Thickness in the length direction z at the center in the height direction x of the Ni plating layer located on the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 3 μm Thickness at the center in the longitudinal direction z of the Ni plating layer located on the first principal surface, the second principal surface, and the first side surface, and the second side surface: 3 μm ·Thickness of Sn plating layer Thickness in the length direction z at the center in the height direction x of the Ni plating layer located on the first end face and the second end face in the cross section of the laminate at the 1 / 2W position: 4 μm Thickness at the center in the longitudinal direction z of the Ni plating layer located on the first principal surface, the second principal surface, and the first side surface, and the second side surface: 4 μm
[0125] (e) Method for measuring the content ratio of metal filler constituting the metal component in the end face side conductive resin layer The content ratio of the metal filler constituting the metal component in the end face side conductive resin layer was measured on a cross section as shown below. That is, first, polishing was started from the first or second side of the multilayer ceramic capacitor sample, and the center of the height direction x of the end face side conductive resin layer on the first or second end face side was confirmed on the LT surface polished to a position that is 1 / 2W of the width direction y connecting the first and second side faces. Alternatively, polishing was started from the first or second main surface of the multilayer ceramic capacitor sample, and the center of the width direction y of the end face side conductive resin layer on the first or second end face side was confirmed on the LW surface polished to a position that is 1 / 2T of the height direction x connecting the first and second main surfaces. Next, a backscattered electron image was observed and photographed using a scanning electron microscope (SEM) at an accelerating voltage of 5 kV and a magnification of 1000 times so that the thermosetting resin and other parts (metal component (metal filler), voids) could be distinguished. The captured image was then binarized using image analysis software to separate the thermosetting resin from the other parts, and the metal component content in the end face conductive resin layer was calculated. The number of observations, n, was set to 100, and the average value was taken as the metal component content in the end face conductive resin layer.
[0126] (f) Method for measuring the content ratio of resin components in the end face side conductive resin layer The content ratio of the resin component in the adjacent conductive resin layer was measured on a cross section as shown below. That is, first, polishing was started from the first or second side of the multilayer ceramic capacitor sample, and the center of the length direction z of the adjacent conductive resin layer on the first or second main surface side was confirmed on the LT surface polished to a position that is 1 / 2W of the width direction y connecting the first and second side surfaces. Alternatively, polishing was started from the first or second main surface of the multilayer ceramic capacitor sample, and the center of the length direction z of the adjacent conductive resin layer on the first or second side surface side was confirmed on the LW surface polished to a position that is 1 / 2T of the height direction x connecting the first and second main surfaces. Next, a backscattered electron image was observed and photographed with a scanning electron microscope (SEM) at an accelerating voltage of 5 kV and a magnification of 1000 times so that the thermosetting resin and other parts (metal components (metal filler), voids) could be distinguished. The captured image was then binarized using image analysis software to separate the thermosetting resin from the other components, and the content ratio of the resin component in the adjacent conductive resin layer was calculated. The number of observations, n, was set to 100, and the average value was taken as the content ratio of the resin component in the end face side conductive resin layer.
[0127] (g) Method for measuring the content ratio of metal filler constituting the metal component in the adjacent conductive resin layer The method for measuring the content ratio of the metal component in the adjacent conductive resin layer was as follows: the measurement was performed on a cross section. That is, first, polishing was started from the first or second side of the sample multilayer ceramic capacitor, and the center of the height direction x of the adjacent conductive resin layer on the first or second main surface side was confirmed on the LT surface polished to a position that is 1 / 2W of the width direction y connecting the first and second side surfaces. Alternatively, polishing was started from the first or second main surface of the sample multilayer ceramic capacitor, and the center of the length direction z of the adjacent conductive resin layer on the first or second side surface side was confirmed on the LW surface polished to a position that is 1 / 2T of the height direction x connecting the first and second main surfaces. Next, a backscattered electron image was observed and photographed with a scanning electron microscope (SEM) at an accelerating voltage of 5 kV and a magnification of 1000 times so that the thermosetting resin and other parts (metal components (metal filler), voids) could be distinguished. The captured image was then binarized using image analysis software to separate the thermosetting resin from the other parts, and the content ratio of the metal component in the adjacent conductive resin layer was calculated. The number of observations, n, was set to 100, and the average value was taken as the content ratio of the metal component in the adjacent conductive resin layer.
[0128] (h) Method for measuring the content ratio of resin components in the adjacent conductive resin layer The content ratio of the resin component in the adjacent conductive resin layer was measured on a cross section as shown below. That is, first, polishing was started from the first or second side of the multilayer ceramic capacitor sample, and the center of the length direction z of the adjacent conductive resin layer on the first or second main surface side was confirmed on the LT surface polished to a position that is 1 / 2W of the width direction y connecting the first and second side surfaces. Alternatively, polishing was started from the first or second main surface of the multilayer ceramic capacitor sample, and the center of the length direction z of the adjacent conductive resin layer on the first or second side surface side was confirmed on the LW surface polished to a position that is 1 / 2T of the height direction x connecting the first and second main surfaces. Next, a backscattered electron image was observed and photographed with a scanning electron microscope (SEM) at an accelerating voltage of 5 kV and a magnification of 1000 times so that the thermosetting resin and other parts (metal components (metal filler), voids) could be distinguished. The captured image was then binarized using image analysis software to separate the thermosetting resin from the other components, and the content ratio of the resin component in the adjacent conductive resin layer was calculated. The number of observations, n, was set to 100, and the average value was taken as the content ratio of the resin component in the adjacent conductive resin layer.
[0129] (i) How to check for cracks using a board bending test First, the multilayer ceramic capacitor as a sample was mounted on a mounting board having a thickness of 1.6 mm using solder paste. Then, the substrate was bent from the back side of the mounting substrate on which the multilayer ceramic capacitor was not mounted, using a push rod having a diameter of 5 μm, and mechanical stress was applied. The holding time at this time was 60 seconds, and the bending amount was 17 mm. Note that the conditions in this test were stricter than the normal conditions. After bending the substrate, the multilayer ceramic capacitor was removed from the mounting substrate, and the cross-section was polished to observe whether or not there was a crack inside the laminate. The cross-section was polished so that the LT surface of the multilayer ceramic capacitor was exposed up to a position that was 1 / 2W in the width direction y connecting the first side surface and the second side surface of the multilayer ceramic capacitor. 100 pieces were prepared as each sample of the example and comparative examples 1 to 3. Note that it was determined that there was an effect when there were 20 pieces or less.
[0130] (j) Method for measuring ESR The ESR was measured by the following method. That is, first, before the measurement, the sample multilayer ceramic capacitor was heat-treated in an air atmosphere at 150°C for 1 hour, and then mounted on a measurement board. After 24±2 hours after the completion of the heat treatment, the measurement frequency was set to 1 MHz and the measurement was performed using a network analyzer. 100 pieces were prepared for each of the samples of the embodiment and comparative examples 1 to 3, and the 100 pieces were measured, and the average value was taken as the measured value of the ESR of each sample of the embodiment and comparative examples 1 to 3. A value of 100 mΩ or less was judged to be acceptable.
[0131] (k) Results Table 1 shows the results of confirming the presence or absence of cracks inside the laminate by a substrate bending test and of ESR measurement for each of the samples of the Example and Comparative Examples 1 to 3.
[0132] [Table 1]
[0133] According to Table 1, in the sample of Comparative Example 1, the content ratio of the metal component in the end face side conductive resin layer part and the adjacent conductive resin layer part was both 40%, so the ESR measurement result was 90 mΩ, but the content ratio of the resin component in the end face side conductive resin layer part and the adjacent conductive resin layer part was both 60%, so as a result of checking for the presence or absence of cracks, 20 cracks were generated out of 100 pieces. In Comparative Example 2, the content ratio of the metal component in the end face side conductive resin layer part was 40%, so the ESR measurement result was 90 mΩ, but the content ratio of the resin component in the adjacent conductive resin layer part was relatively low at 30%, so as a result of checking for the presence or absence of cracks, 50 cracks were generated out of 100 pieces. Furthermore, in Comparative Example 3, the conductive resin layer itself was not formed, so the ESR measurement result was 20 mΩ, but as a result of checking for the presence or absence of cracks, 70 cracks were generated out of 100 pieces.
[0134] On the other hand, in the sample of the embodiment, the content ratio of the resin component contained in the adjacent conductive resin layer portion was 60%, and the content ratio of the resin component contained in the end face side conductive resin layer portion was 30%, so the content ratio of the resin component contained in the adjacent conductive resin layer portion was greater than the content ratio of the resin component contained in the end face side conductive resin layer portion, and as a result, the ESR measurement result was 25 mΩ, which was good, and the check for the presence or absence of cracks showed 0 out of 100, which was a good result.
[0135] From the above results, according to the structure of the multilayer ceramic capacitor of the example, when the total of the resin component and the metal component in the end face side conductive resin layer portion and the adjacent conductive resin layer portion is taken as 100%, the content ratio of the resin component contained in the adjacent conductive resin layer portion is higher than the content ratio of the resin component contained in the end face side conductive resin layer portion, so that conductivity is ensured, a relatively low ESR is obtained, and the occurrence of cracks inside the laminate can be suppressed. From the above, it was confirmed that the multilayer ceramic capacitor according to the present invention can have the desired ESR characteristics while having the mechanical strength of a multilayer ceramic capacitor.
[0136] 4. Experimental Example 2 Next, according to the above-mentioned manufacturing method, samples were prepared in which the content ratio of the resin component in each of the end face side conductive resin layer part and the adjacent conductive resin layer part was changed, and evaluation was performed by measuring the ESR and checking the presence or absence of cracks in the laminate by a substrate bending test. The specifications of the sample used in Experimental Example 2 were the same as those of Example 1 in Experimental Example 1, except for the content ratio of the resin component.
[0137] (a) Sample used in Experimental Example 2 As shown in Table 2, the samples of sample numbers 1 to 7 have a resin component content of 5% in the end face side conductive resin layer portion and the resin component content of the adjacent conductive resin layer portion is changed, the samples of sample numbers 8 to 15 have a resin component content of 10% in the end face side conductive resin layer portion and the resin component content of the adjacent conductive resin layer portion is changed, and the samples of sample numbers 16 to 22 have a resin component content of 30% in the end face side conductive resin layer portion and the resin component content of the adjacent conductive resin layer portion is changed. Samples No. 23 to No. 26 had a resin component content of 40% in the end face side conductive resin layer portion and the resin component content of the adjacent conductive resin layer portion was varied, samples No. 27 to No. 31 had a resin component content of 60% in the end face side conductive resin layer portion and the resin component content of the adjacent conductive resin layer portion was varied, and samples No. 32 to No. 35 had a resin component content of 65% in the end face side conductive resin layer portion and the resin component content of the adjacent conductive resin layer portion was varied.
[0138] (b) Experimental method The method for checking the presence or absence of cracks inside the laminate and the method for measuring the ESR were the same as in Experimental Example 1.
[0139] (c) Results Table 2 shows the results of checking for the presence or absence of cracks inside the laminate by a substrate bending test for each of sample numbers 1 to 35, and of measuring the ESR.
[0140] [Table 2]
[0141] In each of the samples No. 1 to No. 7, the resin component content of the end face side conductive resin layer was 5%, which is less than 10%, and therefore the ESR value was 110 mΩ. This indicates that there is a necessary content ratio of the resin component of the end face side conductive resin layer apart from the content ratio of the resin component of the adjacent conductive resin layer. In the samples No. 1 and No. 2, the resin component content ratio of the end face side conductive resin layer is equal to or greater than the content ratio of the resin component of the adjacent conductive resin layer, and both the resin component content ratio of the end face side conductive resin layer and the resin component content ratio of the adjacent conductive resin layer are relatively low. Therefore, in the sample No. 1, 100 out of 100 samples had cracks inside the laminate, and in the sample No. 2, 90 out of 100 samples had cracks inside the laminate. In addition, in each of samples No. 3 to No. 7, the ESR was 110 mΩ, but since the content ratio of the resin component in the adjacent conductive resin layer was 10% or more, the number of samples with cracks inside the laminate in each sample number was relatively small, at 20 or less out of 100 samples.
[0142] In each of the samples No. 8 to No. 15, the resin component content of the end face side conductive resin layer portion was 10%, but in the samples No. 8 and No. 9, the resin component content of the end face side conductive resin layer portion was equal to or greater than the resin component content of the adjacent conductive resin layer portion, so that in the sample No. 8, 90 out of 100 samples had cracks inside the laminate, and in the sample No. 9, 80 out of 100 samples had cracks inside the laminate. On the other hand, in the samples No. 10 to No. 15, the ESR was 20 mΩ and 100 mΩ or less, and in each of the samples No. 10 to No. 15, the number of samples with cracks inside the laminate was relatively small, at 15 out of 100 or less. In particular, in the samples No. 11 to No. 14, the resin component content of the adjacent conductive resin layer portion was 40% or more and 90% or less, so that in the samples No. 100, 0 samples had cracks.
[0143] In each of samples No. 16 to No. 22, the resin component content of the end face side conductive resin layer portion is 30%, but in samples No. 16 and No. 17, the resin component content of the end face side conductive resin layer portion is equal to or greater than the resin component content of the adjacent conductive resin layer portion, so that in sample No. 16, 80 out of 100 samples had cracks inside the laminate, and in sample No. 17, 50 out of 100 samples had cracks inside the laminate. On the other hand, in samples No. 18 to No. 22, the ESR was 25 mΩ and 100 mΩ or less, and in each sample No., the number of samples with cracks inside the laminate was relatively small, at 10 or less out of 100. In particular, in sample numbers 18 to 21, the content ratio of the resin component in the adjacent conductive resin layer was 40% or more and 90% or less, so 0 out of 100 samples had cracks.
[0144] In each of the samples No. 23 to No. 26, the resin component content of the end face side conductive resin layer was 40%, but in the sample No. 23, the resin component content of the end face side conductive resin layer was equal to or greater than the resin component content of the adjacent conductive resin layer, so that in the sample No. 23, cracks occurred inside the laminate in 50 out of 100 samples. On the other hand, in the samples No. 24 to No. 26, the ESR was 45 mΩ and 100 mΩ or less, and in each sample No., the number of samples in which cracks occurred inside the laminate was relatively small, at 15 or less out of 100 samples. In particular, in the samples No. 24 and No. 25, the resin component content of the adjacent conductive resin layer was 40% or more and 90% or less, so that in the sample No. 25, the number of samples in which cracks occurred was 0 out of 100 samples.
[0145] In each of the samples No. 27 to No. 31, the resin component content of the end face side conductive resin layer was 60%, but in the samples No. 27 and No. 28, the resin component content of the end face side conductive resin layer was equal to or greater than the resin component content of the adjacent conductive resin layer, so that in the sample No. 27, 50 out of 100 samples had cracks inside the laminate, and in the sample No. 28, 20 out of 100 samples had cracks inside the laminate. On the other hand, in the samples No. 29 to No. 31, the ESR was 90 mΩ and 100 mΩ or less, and in each sample No., the number of samples with cracks inside the laminate was relatively small, 15 out of 100 or less. In particular, in the samples No. 29 and No. 30, the resin component content of the adjacent conductive resin layer was 40% or more and 90% or less, so that in the samples No. 100, 0 samples had cracks.
[0146] In each of samples No. 32 to No. 35, the resin component content of the end face side conductive resin layer was 65%, so the ESR value was 120 mΩ. In each of samples No. 32 to No. 35, the resin component content of the end face side conductive resin layer was 65%, so in each of the samples with sample numbers, the number of samples in which cracks occurred inside the laminate was relatively small, at 15 or less out of 100 samples.
[0147] From the above results, it was confirmed that a multilayer ceramic capacitor having a desired ESR and not causing cracks can be obtained when the content ratio of the resin component in the end surface side conductive resin layer is 10% or more and 60% or less, and when the content ratio of the resin component in the adjacent conductive resin layer is 40% or more and 90% or less, when the total of the resin component and the metal component in the end surface side conductive resin layer is 100%, and when the total of the resin component and the metal component in the adjacent conductive resin layer is 100%, it was confirmed that a multilayer ceramic capacitor having a desired ESR and not causing cracks can be obtained when the content ratio of the metal component in the end surface side conductive resin layer is 40% or more and 90% or less, ....
[0148] As described above, the embodiment of the present invention has been disclosed in the above description, but the present invention is not limited thereto. In other words, various modifications can be made to the above-described embodiment in terms of mechanism, shape, material, quantity, position, arrangement, etc., without departing from the scope of the technical idea and purpose of the present invention, and such modifications are included in the present invention. [Explanation of symbols]
[0149] 10 Multilayer ceramic capacitors 12 Laminate 12a First main surface 12b Second main surface 12c First aspect 12d. Second Aspect 12e First end face 12f Second end face 14 Ceramic layer 16 Internal electrode layer 16a First internal electrode layer 16b Second internal electrode layer 18 Effective layer 20a First outer layer 20b Second outer layer 22a First opposing electrode portion 22b Second opposing electrode portion 22c Counter electrode part 24a First extraction electrode portion 24b Second extraction electrode portion 26 Side (W gap) 28 End (L gap) 30 External electrode 30a First external electrode 30b Second external electrode 32 Base electrode layer 32a First base electrode layer 32b Second base electrode layer 34 Conductive resin layer 34a First conductive resin layer 34a1: First end face side conductive resin layer portion 34a2 first adjacent conductive resin layer portion 34b Second conductive resin layer 34b1 second end face side conductive resin layer portion 34b2 second adjacent conductive resin layer portion 36 Plating layer 36a First plating layer 36b Second plating layer x Height direction y Width direction z Length direction
Claims
1. a laminate including a plurality of laminated ceramic layers, the laminate having a first main surface and a second main surface opposed to each other in a height direction, a first side surface and a second side surface opposed to each other in a width direction perpendicular to the height direction, and a first end surface and a second end surface opposed to each other in a length direction perpendicular to the height direction and the width direction; a first internal electrode layer disposed on the plurality of ceramic layers and exposed at the first end surface; a second internal electrode layer disposed on the plurality of ceramic layers and exposed at the second end surface; a first external electrode electrically connected to the first internal electrode layer and disposed on the first end face, a portion of the first main surface, a portion of the second main surface, a portion of the first side surface, and a portion of the second side surface; a second external electrode electrically connected to the second internal electrode layer and disposed on the second end face, a portion of the first main surface, a portion of the second main surface, a portion of the first side surface, and a portion of the second side surface, the first external electrode and the second external electrode each have a base electrode layer containing a metal component and a glass component, a conductive resin layer containing a metal component and a resin component and disposed on the base electrode layer, and a plating layer disposed on the conductive resin layer; the conductive resin layer has an end surface-side conductive resin layer portion located on the first end surface and the second end surface, and an adjacent conductive resin layer portion extending from an end portion of the end surface-side conductive resin layer portion and located on the first main surface, the second main surface, the first side surface, and the second side surface, a content ratio of the resin component contained in the adjacent conductive resin layer portion is greater than a content ratio of the resin component contained in the end surface side conductive resin layer portion, and a content ratio of the resin component in the end surface side conductive resin layer portion is 10% or more and 60% or less, when a total of the resin component and the metal component in the end surface side conductive resin layer portion and the adjacent conductive resin layer portion is taken as 100%.
2. 2. The multilayer ceramic electronic component according to claim 1, wherein a content ratio of the resin component in the adjacent conductive resin layer portion is 40% or more and 90% or less when a total of the resin component and the metal component in the adjacent conductive resin layer portion is taken as 100%.
3. a content ratio of the metal component in the end surface side conductive resin layer portion is 40% or more and 90% or less when the total of the resin component and the metal component in the end surface side conductive resin layer portion is 100%, 3. The multilayer ceramic electronic component according to claim 1, wherein a content ratio of the metal component in the adjacent conductive resin layer portion is 10% or more and 60% or less when a total of the resin component and the metal component in the adjacent conductive resin layer portion is taken as 100%.
Citation Information
Patent Citations
Laminated ceramic capacitor
JP1999162771A
Multilayer ceramic electronic part
JP2021034440A
Layered ceramic electronic component
JP2021034458A